Conceptual design of the car gear console panel made by glass/natural fiber reinforced hybrid polymer composite - Jameel, Yusuf; Leman, Z.; Sapuan, S. M. (PPIEM, 2022)
This study was conducted in order to enhance the quality of car gear console panel with environmentally friendly aspects by making it from glass/coir fiber-reinforced polypropylene hybrid composite. The functions and competitive benchmarking criteria were compiled and merged with the environmental requirements to produce the Product Design Specifications (PDS). The chosen polymer was compared to a benchmark material, Acrylonitrile Butadiene Styrene (ABS), using the Weighted Evaluation Matrix (WEM). Coir fiber and Polypropylene (PP) were found to be effective bio-composites for car gear console panel. After that, using an integrated Theory of Inventive Problem Solving (TRIZ) and Morphological Chart, the conceptual design development of a coir fiber-reinforced polypropylene gear console panel was carried out, fol-lowed by final conceptual design selection utilizing an integrated Pugh Chart. The new design concept has less annular snaps, position of the screws are also changed. Coir fiber-reinforced polypropylene hybrid composites were found to be an alternate material for eco-friendly car gear panel. The final conceptual design of car gear console panel selected on the basis of TRIZ solution which was finalized by using Morphological chart consists of change in the shape of the panel from trapezoidal shape to rectangular shape. The number of annular snaps used was reduced to two from four and number of screws was increased to four from two. Screw positions were distributed evenly on top, bottom, left and right. The assembly structures were kept same as previous that is three.